Da vinci robotic-assisted treatment of pediatric choledochal cyst - Chen, Shan; Lin, Yang; Xu, Di; Lin, Jianli; Zeng, Yunlong; Li, Lizhi (Frontiers in Pediatrics, 2022)
Objective To evaluate the advantages and disadvantages of da Vinci robot and laparoscopy in treating pediatric choledochal cysts. Methods We retrospectively analyzed clinical data from forty-two children diagnosed with choledochal cysts in our hospital from January 2018 to January 2021. Twenty children underwent da Vinci robotic surgery, and the others underwent traditional laparoscopy. We compared differences in general information and preoperative, intraoperative, and postoperative differences between the two surgical groups. Results There was no statistically significant difference in age, gender, weight, type, maximum cyst diameter, preoperative CRP value, postoperative complication rate, and postoperative pain score between the two surgical groups (P>0.05). The average age of the robot-assisted group was 3.62±0.71 years old (range=1-12 years). There were nineteen cases of Todani type I, one patients of other types, and the maximum cyst diameter was 35.45±9.32 mm (range=12-56 mm). In the laparoscopic group, the average age was 3.08±0.82 years old (range=3-10 years). Twenty-one patients had Todani type I, and one had other types. The maximum cyst diameter was 31.94±8.64 mm (range=10-82mm). The robot-assisted group had better abdominal drainage, postoperative C-reactive protein (CRP) value, fasting time, and discharge time than the laparoscopic group (P<0.05). Conclusion Compared with laparoscopy, the da Vinci system has the advantages of less tissue damage, faster recovery, and better healing in the treatment of children with congenital choledochal cysts. With technological advancements and an increased number of experienced surgeons, robotic surgery may become a new trend in surgery.